2017
DOI: 10.3389/fncel.2017.00259
|View full text |Cite
|
Sign up to set email alerts
|

Gp78 E3 Ubiquitin Ligase: Essential Functions and Contributions in Proteostasis

Abstract: As per the requirement of metabolism and fitness, normal cellular functions are controlled by several proteins, and their interactive molecular and signaling events at multiple levels. Protein quality control (PQC) mechanisms ensure the correct folding and proper utilization of these proteins to avoid their misfolding and aggregation. To maintain the optimum environment of complex proteome PQC system employs various E3 ubiquitin ligases for the selective degradation of aberrant proteins. Glycoprotein 78 (Gp78)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 169 publications
(229 reference statements)
0
34
0
Order By: Relevance
“…In the current finding, we have noticed that overexpression of Gp78 influences the endogenous levels of cell cycle regulatory proteins. Previous reports indicate that E3 ubiquitin ligase Gp78 targets various metastasis suppressor and neurodegenerative disease associated proteins for their degradation (Chen et al, ; Joshi, Upadhyay, Kumar, & Mishra, ). It has been observed that tunicamycin treatment induces p27 levels, which suppresses cell cycle progression in melanoma cells (Han, Jin, Mei, & Wu, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the current finding, we have noticed that overexpression of Gp78 influences the endogenous levels of cell cycle regulatory proteins. Previous reports indicate that E3 ubiquitin ligase Gp78 targets various metastasis suppressor and neurodegenerative disease associated proteins for their degradation (Chen et al, ; Joshi, Upadhyay, Kumar, & Mishra, ). It has been observed that tunicamycin treatment induces p27 levels, which suppresses cell cycle progression in melanoma cells (Han, Jin, Mei, & Wu, ).…”
Section: Resultsmentioning
confidence: 99%
“…Toward this end GP78 sequester UBE2G2 to the ER via a specialized helix distal to its RING core, termed the UBE2G2‐binding region (G2BR). G2BR binds to UBE2G2 at UBC backside, extending the canonical E2–E3 contact area and markedly increasing UBE2G2–GP78 interaction affinity …”
Section: Achieving Specificity Beyond the Canonical E2–ring E3 Interamentioning
confidence: 98%
“…G2BR binds to UBE2G2 at UBC backside, extending the canonical E2-E3 contact area and markedly increasing UBE2G2-GP78 interaction affinity. 69 In this noncanonical E2-E3 interaction, R578 and Q579 on G2BR coordinates E31 and N30 on the UBE2G2 β1-β2 loop, while at the other end of G2BR, K600 coordinates E45/E50 on the UBE2G2 β2-β3 loop, clamping the G2BR helix on the UBC backside. Meanwhile, several hydrophobic residues project toward the UBC backside.…”
Section: Specialized E2-ring E3 Interaction Facilitated By Accessormentioning
confidence: 99%
“…cytoplasmic Hsc70-cochaperone, functions with its cognate UbcH5a E2 and Hsc70/Hsp70 in substrate ubiquitination (Ballinger at al., 1999;Connell et al, 2001;Murata et al, 2001;Jiang et al, 2001). gp78/AMFR (autocrine motility factor receptor) is a polytopic, transmembrane cell surface protein (Nabi et al, 1990), as well as ER-integral protein with a cytoplasmic domain containing a RING-finger and other subdomains critical to its recruitment of its cognate E2 (UBC7 or Ube2G2) and catalytic E3-ligase-mediated ubiquitination role (Fang et al, 2001;Chen et al, 2012;Joshi et al, 2017).…”
Section: Significance Statementmentioning
confidence: 99%